Experiences of coercion amongst involuntary mental health care users in KwaZulu-Natal, South Africa - Shozi, Zinhle; Saloojee, Shamima; Mashaphu, Sibongile (Frontiers in Psychiatry, 2023)
Abstract Background: Involuntary admission is a common practice globally. Previous international studies reported that patients experienced high levels of coercion, threats and a range of negative emotions. Little is known about the patients’ experience in South Africa. The aim of this study was to describe the patient’s experiences of involuntary admission at two psychiatric hospitals in KwaZulu-Natal. Methods: A cross-sectional descriptive quantitative study of patients admitted involuntarily was conducted. Demographic information was extracted from clinical records and interviews were conducted with consenting participants at discharge. The MacArthur Perceived Coercion Scale, the MacArthur Negative Pressures Scale, and the MacArthur Procedural Justice Scale, of the MacArthur Admission Experience Survey (short form) were utilised to describe participants’ experiences. Results: This study comprised 131 participants. The response rate was 95.6%. Most participants (n= 96; 73%) experienced high levels of coercion and threats (n= 110; 84%) on admission. About half (n= 61; 46.6%) reported that they felt unheard. Participants reported feeling sad (n= 68; 52%), angry (n= 54; 41.2%) and confused (n= 56; 42.7%). There was a significant association between good insight and a feeling of relief (p=0.001), and between poor insight and feelings of anger (p=0.041). Conclusion: The findings of this study confirm that most patients who were admitted involuntarily experienced high levels of coercion, threats and exclusion from the decision-making process. Patient involvement and control of the decision-making process must be facilitated to improve clinical and overall health outcomes. The need for involuntary admission must justify the means.